2014
DOI: 10.1093/hmg/ddu216
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 suppresses CGG repeat-induced neurotoxicity through interactions with HnRNP A2/B1

Abstract: Nucleotide repeat expansions can elicit neurodegeneration as RNA by sequestering specific RNA-binding proteins, preventing them from performing their normal functions. Conversely, mutations in RNA-binding proteins can trigger neurodegeneration at least partly by altering RNA metabolism. In Fragile X-associated tremor/ataxia syndrome (FXTAS), a CGG repeat expansion in the 5'UTR of the fragile X gene (FMR1) leads to progressive neurodegeneration in patients and CGG repeats in isolation elicit toxicity in Drosoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 79 publications
2
53
0
Order By: Relevance
“…Previous reports suggested that TDP-43 suppression of CGG repeat toxicity is dependent on hnRNPA2B1 orthologues in an FXTAS fly model (He et al, 2014). On the other hand, hnRNPA2B1 suppression of CGG repeat toxicity was reported to be independent of a TDP-43 orthologue (He et al, 2014).…”
Section: Resultsmentioning
confidence: 96%
“…Previous reports suggested that TDP-43 suppression of CGG repeat toxicity is dependent on hnRNPA2B1 orthologues in an FXTAS fly model (He et al, 2014). On the other hand, hnRNPA2B1 suppression of CGG repeat toxicity was reported to be independent of a TDP-43 orthologue (He et al, 2014).…”
Section: Resultsmentioning
confidence: 96%
“…Interestingly, it was found that ALS-causing mutations of TDP-43 enhanced the phenotypes associated with FXTAS. In addition, phenotypic suppression by TDP-43 appears to be through an interaction with Heterogeneous nuclear ribonucleoprotein A2B1 (hnRNPA2B1), suggesting a link between these two RNA-binding proteins and FXTAS (He et al, 2014). …”
Section: 0 Drosophila Models Of Alsmentioning
confidence: 99%
“…The same group also reported that a reduction in nuclear hnRNPA3 leads to an increased level of C9orf72 repeat RNA foci and dipeptide protein repeats in ALS/FTD and ALS patient hippocampal tissues, as well as in ALS patient fibroblasts positive for the expansion [9]. In neurons and oligodendrocytes, hnRNPA3 has an affinity to the 21-nt hnRNPA2 response element (A2RE), which is essential for the export of several mRNAs from the nucleus to the cytoplasm [22,23]. In the neurites of cultured hippocampal neurons, microinjected A2RE-RNA was found to co-localise with hnRNPA3 in cytoplasmic RNA granules, suggesting a role of hnRNPA3 in RNA trafficking [22].…”
Section: Discussionmentioning
confidence: 99%